Detection of therapeutic radiation in three-dimensions - Adamovics, John A. (Beilstein Journal of Organic Chemistry, 2017)
For over the last twenty years there has been a multitude of sophisticated three-dimensional radiation delivery procedures developed which requires a corresponding verification of the impact on patients. This article reviews the state of the art in the development of chemical detectors used to characterize the three-dimensional shape of therapeutic radiation. These detectors are composed of polyurethane, radical initiator and a leuco dye, which is radiolytically oxidized to a dye absorbing at 630 nm.
Keywords: dosimeters; leuco dyes; polymers; radiation; triarylmethane synthesis